A method for strengthening the synchronous harmless of iron manganese valuable metals and residue in leaching electrolytic manganese residue

CN122979634APending Publication Date: 2026-10-27CHONGQING UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611236542.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]本发明的目的在于克服现有电解锰渣铁锰浸出技术存在的浸出效率低、选择性差、酸耗高、体系易钝化、药剂成本高及环境安全性不足等缺陷,提供一种硫酸-铜粉协同强化浸出电解锰渣中铁锰有价金属和降低浸出渣毒性的方法

Benefits of technology

[0016]本发明方法通过加入稀硫酸和含铜物质,硫酸-铜在体系中产生协同作用,显著提高了电解锰渣中铁和锰的浸出率,同时浸出渣中Mn2+与NH4+-N浸出毒性大幅降低,实现有价金属高效回收与渣体同步无害化。本发明方法兼具资源回收与环境治理双重效益,工艺条件温和、流程简便,具备良好的工业化应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979634A_ABST
    Figure CN122979634A_ABST
Patent Text Reader

Abstract

The application discloses a method for synchronously harmless treatment of iron and manganese valuable metals and slag in reinforced leaching electrolytic manganese residue, and relates to the technical field of industrial solid waste resource utilization. The method comprises the following steps: adding fine-grained electrolytic manganese residue into a dilute sulfuric acid solution, uniformly stirring and dispersing, and then adding a copper-containing substance; under the conditions of heating and stirring, reaction is carried out to obtain leaching ore slurry; and then the leaching ore slurry is filtered and washed to obtain an iron and manganese-rich leaching solution and a low-toxicity leaching residue. In the method, sulfuric acid and copper have a synergistic effect, which significantly improves the leaching rate of iron and manganese, and the leaching residue has a low Mn 2+ and NH4 + -N leaching toxicity, and the valuable metals are efficiently recovered and the residue is synchronously harmless treated. The method has dual benefits of resource recovery and environmental governance, has mild process conditions and a simple process, and has a good industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of industrial solid waste resource utilization technology. It relates to an efficient method for recovering valuable iron and manganese metals from electrolytic manganese slag, specifically a method for the simultaneous harmless treatment of valuable iron and manganese metals and the slag itself through sulfuric acid-copper enhanced leaching. Background Technology

[0002] Electrolytic manganese slag is an acidic industrial solid waste generated during the electrolytic manganese metal production process, after manganese ore undergoes sulfuric acid leaching, purification, and pressure filtration. It is characterized by large quantities, complex composition, high salt content, and stable heavy metal deposition. my country is a major global producer and consumer of electrolytic manganese metal, generating approximately 8-12 tons of electrolytic manganese slag for every ton of electrolytic manganese produced. Currently, the national stockpile exceeds 170 million tons, and continues to grow at a rate of nearly 10 million tons per year. This large-scale stockpiling not only occupies land resources but also poses environmental risks such as sulfate leaching, heavy metal migration, and ammonia nitrogen release, becoming a prominent issue hindering the green and sustainable development of the manganese industry.

[0003] Electrolytic manganese slag contains valuable metals such as iron and manganese. Efficiently recovering these metals and realizing the resource utilization of the slag is the core direction for the harmless, reduced-volume, and high-value utilization of electrolytic manganese slag. Currently, the technology for extracting iron and manganese from electrolytic manganese slag mainly relies on wet leaching, with dilute sulfuric acid leaching being the most widely used industrial method due to its simplicity, mild conditions, and wide applicability. However, traditional single sulfuric acid leaching has significant technical shortcomings: iron and manganese in electrolytic manganese slag are mostly in the form of Fe. 3 + Mn 4+ The presence of high-valence, insoluble oxides, hydroxides, and silicate compounds limits the solubility of dilute acids, resulting in low leaching rates of iron and manganese and low resource utilization. Increasing the acid concentration to improve leaching efficiency leads to the dissolution of large amounts of impurities such as calcium, magnesium, silicon, and aluminum, making the leaching solution system complex, increasing separation difficulty, and exacerbating equipment corrosion and reagent consumption, resulting in poor economic efficiency.

[0004] Therefore, this invention provides a method for the simultaneous harmless treatment of valuable iron and manganese metals and slag in electrolytic manganese slag by synergistic enhancement of sulfuric acid-copper element leaching, in order to solve the problems of low leaching rate, poor selectivity, high acid consumption, easy passivation, and insufficient safety in the existing technology, and to achieve efficient recovery of iron and manganese and resource utilization of slag. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of existing electrolytic manganese slag leaching technologies, such as low leaching efficiency, poor selectivity, high acid consumption, easy passivation of the system, high reagent costs, and insufficient environmental safety. This invention provides a method for synergistically enhancing the leaching of valuable iron and manganese metals in electrolytic manganese slag using sulfuric acid and copper powder, and reducing the toxicity of the leaching residue. This method achieves efficient reduction and dissolution of high-valent iron and manganese minerals through the synergistic effect of dilute sulfuric acid and copper-containing substances, significantly improving the leaching rate and selectivity of iron and manganese, and simultaneously rendering the slag harmless. It also possesses advantages such as simple process, mild conditions, no toxic byproducts, and smooth solid-liquid separation, making it suitable for large-scale industrial application.

[0006] To achieve the above objectives, this invention provides a method for enhancing the extraction of valuable iron and manganese metals from leaching electrolytic manganese slag while ensuring the slag remains harmless. The main process is as follows: Figure 1 As shown, it includes the following steps:

[0007] 1) Pretreatment: The electrolytic manganese slag is dried in an oven at 105℃ to constant weight, and then ground and passed through a 200-mesh sieve to obtain fine-grained electrolytic manganese slag;

[0008] 2) Co-leaching: Fine-grained electrolytic manganese slag is added to a dilute sulfuric acid solution and stirred to disperse it evenly. Then, copper-containing substances are added. Under heating and stirring conditions, a sulfuric acid-copper element co-leaching reaction is carried out. Through the reduction effect of copper-containing substances and potential regulation, high-valence iron and manganese minerals are rapidly dissolved to obtain leaching slurry. The copper-containing substances are substances containing copper elements and can be elements, compounds, or mixtures.

[0009] 3) Solid-liquid separation: The leaching slurry is filtered and washed to obtain an iron- and manganese-rich leaching solution and a low-toxicity leaching residue. The low-toxicity refers to the low Mn content in the leaching residue. 2+ and NH4 + The content of -N is low.

[0010] Preferably, the mass fraction of the dilute sulfuric acid in step 2) is 2-10%.

[0011] Preferably, in step 2), the liquid-to-solid ratio of the dilute sulfuric acid solution to the fine electrolytic manganese slag in the dilute sulfuric acid solution is 5:1 to 9:1 mL / g.

[0012] Preferably, the copper-containing substance in step 2) includes any one or more of copper powder, CuCl, and CuSO4·5H2O.

[0013] Preferably, the amount of copper-containing substance added in step 2) is 1% to 5% of the mass of the electrolytic manganese slag.

[0014] Preferably, in step 2), the heating temperature is 60 °C, the stirring rate is 400 r / min, and the reaction time is 60 min.

[0015] Preferably, in step 2), the copper-containing substance is copper powder with a purity ≥90%; the mass fraction of the dilute sulfuric acid is 2%; the liquid-to-solid ratio of the dilute sulfuric acid solution to the fine electrolytic manganese slag in the dilute sulfuric acid solution is 7:1 mL / g; the amount of copper-containing substance added is 1% of the mass of the electrolytic manganese slag; the heating temperature is 60 ℃; the stirring rate is 400 r / min; and the reaction time is 60 min.

[0016] The method of this invention, by adding dilute sulfuric acid and copper-containing substances, achieves a synergistic effect between sulfuric acid and copper in the system, significantly improving the leaching rates of iron and manganese in electrolytic manganese slag, while simultaneously reducing the amount of Mn in the leaching slag. 2+ With NH4 + The leaching toxicity of -N is significantly reduced, achieving efficient recovery of valuable metals and simultaneous harmless treatment of the slag. This invention offers dual benefits of resource recovery and environmental remediation, with mild process conditions and a simple procedure, demonstrating promising prospects for industrial application. Attached Figure Description

[0017] Figure 1 This is a flowchart of the co-leaching process of electrolytic manganese slag according to the present invention, wherein copper powder can be replaced with other copper-containing substances;

[0018] Figure 2 The XRD pattern of the electrolytic manganese slag of this invention;

[0019] Figure 3 This is a SEM image of the electrolytic manganese slag before and after leaching, where (a) is the original electrolytic manganese slag and (b) is the leaching residue. Detailed Implementation

[0020] The present invention will be described in detail below with reference to embodiments. These embodiments are for illustrative purposes only and are not intended to limit the scope of application of the present invention. The present invention is not limited to the following embodiments or examples. Any modifications and variations made without departing from the spirit of the present invention should be included within the scope of the present invention. Unless otherwise specified, the experimental materials or reagents used in the following embodiments are all conventional commercially available products or can be obtained by known methods.

[0021] The electrolytic manganese slag was obtained from Guizhou Jinrui New Materials Co., Ltd.

[0022] Electrolytic manganese slag was dried in an oven at 105 °C to constant weight, then ground and passed through a 200-mesh sieve to obtain fine-grained electrolytic manganese slag. The main chemical components of the electrolytic manganese slag are SiO2, SO3, CaO, Al2O3, Fe2O3, MgO, and MnO, with the mass percentages of each component shown in Table 1 (original slag). XRD characterization of the electrolytic manganese slag samples is as follows: Figure 1As shown, it mainly contains CaSO4·2H2O phase and SiO2 phase, as well as ammonium magnesium manganese complex salt, hydrotalcite, and chlorite silicate minerals. The main pollutants in electrolytic manganese slag are manganese and ammonia nitrogen. The leaching toxicity of electrolytic manganese slag was tested, and the leaching concentrations were 1450 mg / L and 596 mg / L, respectively (referring to the "Leaching Toxicity of Solid Waste - Horizontal Oscillation Method" (HJ 557-2010)).

[0023] The calculation of iron and manganese leaching rates is based on the metal content in the raw materials and leachate, and the calculation formula is as follows: , where η is the leaching rate of the target metal (%); C is the mass concentration of the target metal in the leachate (mg / L), determined by ICP-OES; V is the total volume of the leachate (L); m0 is the dry basis mass of the electrolytic manganese slag raw material (g); and w is the mass fraction of the target metal in the raw material.

[0024] Example 1

[0025] 5 kg of fine-grained electrolytic manganese slag was weighed and added to 35 L of pure water at a liquid-to-solid ratio of 7:1 L / kg. The mixture was stirred and dispersed evenly, and reacted at 60℃ and a stirring rate of 400 r / min for 60 min. After the reaction, the residue was filtered and washed to obtain the leachate and leaching residue. The manganese leaching rate was found to be 30.40%, and the iron leaching rate was 12.58%. The leaching residue was rinsed with pure water and then subjected to leaching toxicity testing. The measured Mn content in the leaching residue was... 2+ The content was 489.10 mg / L, NH4 + The -N content was 289.50 mg / L.

[0026] Example 2

[0027] 5 kg of fine-grained electrolytic manganese slag was weighed and added to 35 L of a 2 wt.% (2% by mass) dilute sulfuric acid solution at a liquid-to-solid ratio of 7:1 mL / g. The mixture was stirred and dispersed evenly, and reacted at 60℃ and a stirring rate of 400 r / min for 60 min. After the reaction was completed, the mixture was filtered and washed to obtain the leachate and leaching residue. The manganese leaching rate was tested to be 68.84%, and the iron leaching rate was 35.56%. The leaching residue was rinsed with pure water and then subjected to leaching toxicity testing. The measured Mn content in the leaching residue was... 2+ The content was 178.50 mg / L, NH4 + The -N content was 136.9 mg / L.

[0028] Example 3

[0029] 5 kg of fine-grained electrolytic manganese slag was weighed and added to 35 L of 2 wt.% dilute sulfuric acid solution at a liquid-to-solid ratio of 7:1 mL / g. After stirring and dispersing evenly, 50 g of copper powder with a purity ≥99.5% was added. The reaction was carried out at 60℃ and a stirring rate of 400 r / min for 60 min. After the reaction, the mixture was filtered and washed to obtain an iron-rich manganese leaching solution and a low-impurity leaching residue. The manganese leaching rate was tested to be 89.60%, and the iron leaching rate was 62.35%. The leaching residue was rinsed with pure water and then subjected to leaching toxicity testing. The measured Mn content in the leaching residue was... 2+ The content was 23.10 mg / L, NH4 + The -N content was 87.30 mg / L.

[0030] Example 4

[0031] 5 kg of fine-grained electrolytic manganese slag was weighed and added to 35 L of 2 wt.% dilute sulfuric acid solution at a liquid-to-solid ratio of 7:1 mL / g. After stirring and dispersing evenly, 50 g of CuCl (monovalent copper ions) was added. The reaction was carried out at 60℃ and a stirring rate of 400 r / min for 60 min. After the reaction, the mixture was filtered and washed to obtain an iron-rich manganese leaching solution and a low-impurity leaching residue. The manganese leaching rate was tested to be 72.17%, and the iron leaching rate was 45.58%. The leaching residue was rinsed with pure water and then subjected to leaching toxicity testing. The measured Mn content in the leaching residue was... 2+ The content was 83.81 mg / L, NH4 + The -N content is 110.50 mg / L.

[0032] Example 5

[0033] 5 kg of fine-grained electrolytic manganese slag was weighed and added to 35 L of 2 wt.% dilute sulfuric acid solution at a liquid-to-solid ratio of 7:1 mL / g. After stirring and dispersing evenly, 50 g of CuSO4·5H2O (divalent copper ions) was added. The reaction was carried out at 60℃ and a stirring rate of 400 r / min for 60 min. After the reaction, the mixture was filtered and washed to obtain an iron-rich manganese leaching solution and a low-impurity leaching residue. The manganese leaching rate was found to be 75.29%, and the iron leaching rate was 49.33%. The leaching residue was rinsed with pure water and then subjected to leaching toxicity testing. The measured Mn content in the leaching residue was... 2+ The content was 79.57 mg / L, NH4 + -N content was 109.40 mg / L.

[0034] Example 6

[0035] 5 kg of fine-grained electrolytic manganese slag was weighed and added to 35 L of 2 wt.% dilute sulfuric acid solution at a liquid-to-solid ratio of 7:1 mL / g. After stirring and dispersing evenly, 25 g of copper powder with a purity ≥99.5% was added. The reaction was carried out at 60℃ and a stirring rate of 400 r / min for 60 min. After the reaction, the mixture was filtered and washed to obtain an iron-rich manganese leaching solution and a low-impurity leaching residue. The manganese leaching rate was tested to be 72.38%, and the iron leaching rate was 43.08%. The leaching residue was rinsed with pure water and then subjected to leaching toxicity testing. The measured Mn content in the leaching residue was... 2+ The content was 126.70 mg / L, NH4 + -N content is 103.50 mg / L.

[0036] Example 7

[0037] 5 kg of fine-grained electrolytic manganese slag was weighed and added to 35 L of 6 wt.% dilute sulfuric acid solution at a liquid-to-solid ratio of 7:1 mL / g. After stirring and dispersing evenly, 50 g of copper powder with a purity ≥99.5% was added. The reaction was carried out at 60℃ and a stirring rate of 400 r / min for 60 min. After the reaction was completed, the mixture was filtered and washed to obtain the leaching solution and leaching residue. The manganese leaching rate was tested to be 93.09%, and the iron leaching rate was 66.63%. The leaching residue was rinsed with pure water and then subjected to leaching toxicity testing. The measured Mn content in the leaching residue was... 2+ The content was 13.80 mg / L, NH4 + -N content is 86.50 mg / L.

[0038] Example 8

[0039] 5 kg of fine-grained electrolytic manganese slag was weighed and added to 35 L of 6 wt.% dilute sulfuric acid solution at a liquid-to-solid ratio of 7:1 mL / g. After stirring and dispersing evenly, 150 g of copper powder with a purity ≥99.5% was added. The reaction was carried out at 60℃ and a stirring rate of 400 r / min for 60 min. After the reaction, the mixture was filtered and washed to obtain the leaching solution and leaching residue. The manganese leaching rate was tested to be 97.37%, and the iron leaching rate was 77.85%. The residue was rinsed with pure water and then subjected to leaching toxicity testing. The measured Mn content in the leaching residue was... 2+ The content is 7.80 mg / L, NH4 + The -N content was 63.10 mg / L.

[0040] As shown in Table 1, the XRF analysis of electrolytic manganese slag before and after the synergistic leaching treatment with sulfuric acid and copper powder according to this invention revealed significant changes in the chemical composition of the electrolytic manganese slag. The contents of MnO and Fe2O3 in the original slag decreased from 2.63 wt.% and 3.98 wt.%, respectively, to 0.053 wt.% and 0.574 wt.% in the leached slag. Impurities such as SO3, CaO, and MgO also decreased significantly. The SEM analysis showed a significant change in the chemical composition of the electrolytic manganese slag before and after the treatment. Figure 3It can be seen that the dense and smooth columnar and plate-shaped crystals in the raw residue are dissolved and destroyed, and the surface of the leaching residue particles becomes rough and porous, which further verifies the high efficiency of the process for leaching valuable metals such as iron and manganese, and also creates favorable conditions for the subsequent resource utilization of the leaching residue.

[0041] Table 1. Percentage of major compounds in electrolytic manganese slag before and after leaching (wt%)

[0042]

[0043] In the above embodiments, the leaching rates of manganese and iron and the amount of Mn in the leaching residue were as follows: 2+ With NH4 + The -N content is shown in Table 2:

[0044] Table 2. Manganese and iron leaching rates and Mn content in leaching residue in the examples. 2+ With NH4 + -N content

[0045]

[0046] In summary, direct leaching of electrolytic manganese slag with pure water results in low iron and manganese leaching rates and high toxicity of the leached residue. While leaching with dilute sulfuric acid alone can improve the leaching effect to some extent, it still fails to achieve efficient recovery and harmless treatment of the slag. This invention utilizes the synergistic effect of sulfuric acid and copper, especially with copper powder, leveraging the reducing properties and potential control of copper powder to convert sparingly soluble high-valent iron and manganese into easily soluble divalent ions, significantly enhancing the leaching effect. With optimization of sulfuric acid concentration and copper powder addition, the manganese leaching rate can reach up to 97.37%, and the iron leaching rate can reach up to 77.85%. More importantly, the Mn in the leaching residue is significantly reduced. 2+ With NH4 + The leaching toxicity of -N is significantly reduced, achieving efficient recovery of valuable metals and simultaneous harmless treatment of slag. The process is mild, simple, and has outstanding environmental and resource benefits, showing good prospects for industrial application.

[0047] The conventional techniques and solutions not described in detail in the above embodiments are all well known in the art, and therefore will not be elaborated upon here. The above embodiments and / or experimental examples describe the preferred embodiments of the present invention in detail. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solutions of the present invention, and these simple modifications all fall within the protection scope of the present invention.

Claims

1. A method for simultaneously and harmlessly rendering valuable iron and manganese metals and the slag body in enhanced leaching electrolytic manganese slag, characterized in that, Includes the following steps: 1) Pretreatment: The electrolytic manganese slag is dried in an oven at 105 ℃ to constant weight, and then ground and passed through a 200-mesh sieve to obtain fine-grained electrolytic manganese slag; 2) Co-leaching: Fine-grained electrolytic manganese slag is added to a dilute sulfuric acid solution, stirred and dispersed evenly, and then copper-containing substances are added; the reaction is carried out under heating and stirring conditions to obtain leaching slurry; 3) Solid-liquid separation: The leaching slurry is filtered and washed to obtain iron- and manganese-rich leaching solution and low-toxicity leaching residue.

2. The method as described in claim 1, characterized in that, The mass fraction of the dilute sulfuric acid mentioned in step 2) is 2-10%.

3. The method as described in claim 1, characterized in that, In step 2), the liquid-to-solid ratio of the dilute sulfuric acid solution to the fine electrolytic manganese slag in the dilute sulfuric acid solution is 5:1 to 9:1 mL / g.

4. The method as described in claim 1, characterized in that, The copper-containing substances mentioned in step 2) include any one or more of copper powder, CuCl, and CuSO4·5H2O.

5. The method as described in claim 1, characterized in that, The amount of copper-containing substance added in step 2) is 1% to 5% of the mass of the electrolytic manganese slag.

6. The method as described in claim 1, characterized in that, The heating temperature in step 2) is 60 °C, the stirring rate is 400 r / min, and the reaction time is 60 min.

7. The method as described in claim 1, characterized in that, In step 2), the copper-containing substance is copper powder; the mass fraction of the dilute sulfuric acid is 2%; the liquid-solid ratio of the dilute sulfuric acid solution to the fine electrolytic manganese slag in the dilute sulfuric acid solution is 7:1 mL / g; the amount of copper-containing substance added is 1% of the mass of the electrolytic manganese slag; the heating temperature is 60℃; the stirring rate is 400 r / min; and the reaction time is 60 min.